A TEM study of a<001> dislocations in the ßo phase of an intermetallic TNM-TiAl alloy. (15th March 2023) - Molénat, Guy; Monchoux, Jean-Philippe; Musi, Michael; Spoerk-Erdely, Petra; Clemens, Helmut; Couret, Alain
Abstract: The structure and mobility of a<001> dislocations in the β o phase of an intermetallic TNM-TiAl alloy produced by Spark Plasma Sintering were investigated by transmission electron microscopy. We find that these dislocations are dissociated into two identical superpartial dislocations separated by a stacking fault. Furthermore, a<001> dislocations are elongated along their screw orientation and anchored at small pining points assumed to be nano-sized precipitates of the ω o phase. In situ room temperature straining experiments show that dislocation propagation occurs through jumps between these elongated configurations. Graphical abstract: Image, graphical abstract